STUDI KASUS PROSEDUR PEMERIKSAAN COLON IN LOOP DENGAN KLINIS DIARE KRONIS DI INSTALASI RADIOLOGI RSUD PANEMBAHAN SENOPATI BANTUL - Khalifah Evitaria1; Fisnandya Meita Astari; Ildsa Maulidya Mar’atus Nasokha (Bajang Institute, 2025)
Background: Colon in loop (CIL) examination is a radiographic examination with positive or negative retrograde contrast media, which plays an important role in assessing colon disorders, such as chronic diarrhea. According to (Hadjarati et al. 2024), patient preparation is carried out for 48 hours, while in the Radiology Installation of RSUD (Regional General Hospital) Panembahan Senopati Bantul, patient preparation is carried out for 24 hours. According to (Lampignano & Kendrick, 2018), the projections used include AP plan, RPO, RAO, LAO, LLD, RLD, and AP post-evacuation. Meanwhile, the projections used at Senopati Regional Hospital include FPA (plain abdominal radiograph), Lateral, AP post-contrast or lower AP, AP full filling, AP post-contrast negative projections. Method: This research applied a qualitative study with a case study approach. The data collection was conducted at RSUD Panembahan Senopati Bantul. The subjects were one radiologist and three radiographers. The object of the study was a colon in loop examination with clinical chronic diarrhea. Data collection methods used observation, interviews, documentation, and literature. Data analysis used data reduction, data presentation, and conclusion drawing. Results: The results of the study indicated that a colonoscopy in a loop with clinical evidence of chronic diarrhea was performed to confirm the diagnosis of narrowing, mass, or inflammation in the colon. Patient preparation was carried out 24 hours or one day before the examination, then the examination technique was performed using two AP and lateral projections without post-evacuation. Conclusion: A colonoscopy in loop in patients with chronic diarrhea was performed to confirm a diagnosis or assess for colon abnormalities. This examination was performed with 24 hours of patient preparation. The methods included single contrast (200 g barium sulfate/1000 ml water) and double contrast (approximately 300 cc air). The projections used FPA, left lateral, AP with positive contrast, AP with full filling, and AP with negative contrast. These projections were selected to save time, reduce radiation dose, and provide optimal diagnostic capabilities. Informed consent should be obtained before the examination to ensure the patient understands the procedure, benefits, and potential risks. Additionally, the addition of a post-evacuation AP projection is recommended to evaluate residual contrast in the colon and assess intestinal peristalsis